Scatter plots of photo score by ColorDx green cone score (A), red cone score (B), and blue cone score (C). - Richard C. Trevino (22676460) (2025)
CVN: Color vision normal, CVD Color vision deficiency. Photo score: Number of correctly identified photographs.